THE THERMODYNAMIC CHARACTER OF INFORMATION - Popova T.M. (Problems of the Regional Energetics, 2010)
The article includes data concerning application of one of the universal method of the modern science based on fundamental thermodynamic laws to analyze the efficiency of the information processes. The comparison of the information and thermodynamic processes brought the author to the basic conclusion of the energetic character of information.